Advances in condition monitoring of machinery in non-stationary operations : proceedings of the 5th International Conference on Condition Monitoring of Machinery in Non-stationary Operations, CMMNO'2016, 12-16 September 2016, Gliwice, Poland /: proceedings of the 5th International Conference on Condition Monitoring of Machinery in Non-stationary Operations, CMMNO'2016, 12-16 September 2016, Gliwice, Poland. ([2018]) - Unknown
No abstract available